An intimate and imperial feminism: Meliscent Shephard and the regulation of prostitution in colonial India - Legg, Stephen
This paper seeks to construct an antinostalgic portrait of an imperial feminist. As the representative of the Association for Moral and Social Hygiene (AMSH) in India between 1928 and 1947, Meliscent Shephard was an embodiment not only of the feminist urge to challenge patriarchal gender relations, but also of the imperialist urge to classify and fathom the world through a series of racist typologies. Despite an earlier belief that blame for the exploitation of prostitutes lay with the colonial state and economy, she later fell back on explanations based on notions of Indian society and religion. Operating in a period of heightened anticolonial nationalism, these latter views thwarted any hope of her forging successful connections with emergent Indian social reform groups. This failure to cultivate intimate relations with Indian colleagues marks a failure at the level of national and racial politics. Shephard did, however, cultivate an intimate relationship with correspondents at the AMSH in London, while her experiences of the sexual geographies of Indian cities provided a form of intimate interaction that would inspire her mission to close down tolerated brothels. As such, this paper marks an empirical engagement with the intimate frontiers at which the affective grid of colonial politics was marked out.